Electrocatalytic degradation of sulfamethazine on IrO2-RuO2 composite electrodes: influencing factors, kinetics and modeling. Issue 4 (August 2021) - Yu, Naichuan; Lu, Xinyu; Song, Fei; Yao, Yingwu; Han, Enshan
Abstract: In this study, IrO2 -RuO2 composite electrodes were prepared and well characterized. The electrode exhibited a compact structure, with the IrO2 -RuO2 binary oxide coatings appearing as finely dispersed crystals. The IrO2 -RuO2 composite electrodes were used as the anode to degrade sulfamethazine (SMT) via the indirect oxidation process of hydroxyl radicals. The optimum degradation conditions of SMT were as follows: initial concentration: 50 mg/L; current density: 40 mA/cm 2 and initial pH: 6.0 at a supporting electrolyte (Na2 SO4 )concentration of 0.2 mol/L. The IrO2 -RuO2 composite electrodes effectively removes chemical oxygen demand (COD) from actual wastewater: the removal rate was 49.17%. The after-treatment COD value was 107.83 mg/L lower than China's urban sewage COD discharge standard (120 mg/L). These results indicate that the electrocatalytic degradation of SMT with electrodes is feasible. Besides, the effects of the experimental conditions on the sensitivity of the experiment were studied by using an established mathematical model and an artificial neural network (ANN) model representing the first time, which can be used to effectively predict and guide the removal of COD from SMT-containing wastewater using IrO2 -RuO2 composite electrodes. The modeling results show that reaction time was the most significant factor affecting SMT removal efficiency, whereas pH value was the most important factor affecting COD removal efficiency. Graphical Abstract: ga1 Highlights: IrO2 -RuO2 composite electrode was prepared. Operating parameters were optimized. Mathematical & ANN model were set up.